2016
DOI: 10.1016/j.jalz.2016.06.1147
|View full text |Cite
|
Sign up to set email alerts
|

P1‐395: Progression and Predictors of Mild Cognitive Impairment in Chinese Elderly: A Prospective Follow‐Up in The Shanghai Aging Study

Abstract: Introduction: The Shanghai Aging Study is a community-based study aiming to investigate the incidence and progression of cognitive decline in Chinese elderly, with the operational procedures and diagnostic criteria similar to cohort studies in developed countries. Methods: We prospectively evaluated 362 individuals with mild cognitive impairment (MCI) diagnosed at baseline through a clinical and neuropsychological interview. Diagnoses of dementia and MCI were made using standard criteria via consensus diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…For example, a recent epidemiological study showed that the prevalence of mild cognitive impairment (MCI) in China was 20.1% among older adults aged 60 or above [2]. In addition, it is estimated that around 6% of the older adults with MCI progress to dementia annually [3]. Such increase in cognitive impairment in aging populations have major societal and human implications [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent epidemiological study showed that the prevalence of mild cognitive impairment (MCI) in China was 20.1% among older adults aged 60 or above [2]. In addition, it is estimated that around 6% of the older adults with MCI progress to dementia annually [3]. Such increase in cognitive impairment in aging populations have major societal and human implications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the communitybased Shanghai aging Study investigated the progression of cognitive decline in Chinese elderly 31 . they found that the conversion rate to dementia was 6.0 per 100 personyears, while the reversion rate to cognitive normality was 7.8 per 100 person-years.…”
Section: Discussionmentioning
confidence: 99%
“…In that study, age was considered the main risk factor for developing dementia. evidence from autopsy, epidemiological, and cohort studies show that advanced age is the strongest risk factor for the development of alzheimer's disease related to pathophysiological abnormalities and the ultimate development of symptomatic alzheimer's disease 31 . even so, there is a significant heterogeneity between individuals in the age-specific prevalence of alzheimer's-related pathology: some individuals appear relatively spared from developing the pathognomonic alzheimer's brain lesions even in old age 32 .…”
Section: Discussionmentioning
confidence: 99%
“…10 The CR construct has been formalized by considering two latent variables: level of education (including proxies such as years of formal schooling, occupational attainment, reading habits, and vocabulary knowledge) and lifestyle (including participation in social and cultural activities). 13 Diagnostic transitions in MCI and eventual conversion to dementia have been studied by survival analysis, 14 polynomial regression analysis, 15 multinomial logistic regression (LR) analysis, 16 and Markov models. 13 Diagnostic transitions in MCI and eventual conversion to dementia have been studied by survival analysis, 14 polynomial regression analysis, 15 multinomial logistic regression (LR) analysis, 16 and Markov models.…”
Section: Introductionmentioning
confidence: 99%